2011
DOI: 10.1080/01488376.2011.607367
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Parenting Stress, Perceived Mastery, and Maternal Depression on Parent–Child Interaction

Abstract: The purpose of this study was to test a model that delineated the interrelationships among parenting stress, perceived mastery (defined as the belief that one's life chances are under one's own control), maternal depression, and parent-child interaction. A secondary data analysis of the Fragile Family and Child Well-Being Study was conducted, using a sample of 2,650 mothers. Results suggest that parenting stress undermines one's sense of perceived mastery which, in turn, resulted in depression. Moreover, the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(78 citation statements)
references
References 46 publications
4
68
1
2
Order By: Relevance
“…Other risk factors include feelings of helplessness, hopelessness, extreme fear or anger, and cynicism or distrust of others. Farmer and Lee (2011) found that parenting stress undermines one's sense of perceived mastery, which, in turn, results in depression. They added that parenting stress directly affected maternal depression and parent-child interaction.…”
Section: Stressmentioning
confidence: 97%
“…Other risk factors include feelings of helplessness, hopelessness, extreme fear or anger, and cynicism or distrust of others. Farmer and Lee (2011) found that parenting stress undermines one's sense of perceived mastery, which, in turn, results in depression. They added that parenting stress directly affected maternal depression and parent-child interaction.…”
Section: Stressmentioning
confidence: 97%
“…Therefore, we control for fathers' and mothers' self-reports of their involvement in daily activities with the child, including routine caregiving and play. We control for symptoms of depression as well as parenting stress and alcohol consumption because studies of mothers (Farmer & Lee, 2011;Silverstein, Augustyn, Young, & Zuckerman, 2009;Taylor, Guterman, Lee, & Rathouz, 2009) and fathers (Davis, Davis, Freed, & Clark, 2011;Lee, Perron, Taylor, & Guterman, 2011;Reeb et al, 2014;Wilson & Durbin, 2010) have linked these factors to poorer parenting and physical punishment of young children. Furthermore, maternal distress and depression (Ciciolla, Gerstein, & Crnic, 2013;Goodman et al, 2011;Taylor, Manganello, Lee, & Rice, 2010) are direct and mediating factors linked to the development of child aggression.…”
Section: The Current Studymentioning
confidence: 99%
“…One of the main factors known to have a negative influence on parental functioning is stress (Farmer & Lee, 2011;Waylen & Stewart-Brown, 2010). When parents are cognitively and emotionally exhausted, their parental functioning is impaired, and they are less able to mobilize effort, attention, and support for their children (Browne, Meunier, O'Connor, & Jenkins, 2012).…”
Section: Parentingmentioning
confidence: 99%